The empirical importance of precautionary saving in Turkey - Ceritoğlu, Evren (2009)
The aim of this Ph.D. thesis is to contribute to the understanding of household consumption and saving behaviour under risk and uncertainty. The precautionary saving hypothesis proposes that households will postpone their consumption and increase their saving level to be protected against future labour income uncertainty. It is reasonable to interpret the additional rise in household saving due to future labour income uncertainty as precautionary saving. Moreover, it is expected that households will prefer to keep their precautionary saving in the form of financial assets because of their liquidity.